Effect of Mindfulness Based Sport Psychology Counseling on Injured Junior Baseball Players in Rehabilitation Process-Case Study - Yook Young Sook (Asian Society of Kinesiology, 2019)
OBJECTIVES Athletes and other stakeholders tend to focus on their physical aspects of rehabilitation although psychological factors may contribute to the success of return to sports. Therefore, the purpose of this case study was to apply the mindfulness based psychological skills training to injured junior baseball players during the rehabilitation process and examine the effect of the program. METHODS The 8 sessions of the mindfulness based psychological skills training were conducted for 4 participants and K-PCS, K-CAMS-R, Perceived Performance Level, TOPS, PANAS, and CSAI-2 were implemented and analyzed. RESULTS As a result, all of the variables significantly varied in a positive way after the intervention and additionally qualitative results, such as mindfulness and imagery, aided the quantitative result. CONCLUSIONS Such positive effects of the intervention reinforced the importance of the role of psychological rehabilitation for injured athletes, and implication of this study was discussed.